Green Computing: Techniques for Eco-Friendly IT Operations (Global Journal of Computer Science and Technology, 2024)
Attention over the effects of computing on the environment has increased as a result of the increasing demands placed on information technology This paper explores the field of environmentally friendly computing highlighting creative approaches to energy saving and efficient e-waste disposal The study looks at important technologies that are promoting a greener digital environment and investigates the importance of implementing eco-friendly practices in the IT industry To achieve sustainable computing energy-efficient algorithms integration of renewable energy sources and responsible disposal of electronic waste are highlighted as essential elements This study tries to offer a significant understanding of the application of green computing practices and their advantageous environmental effects through case studies and real-world examples
Keywords: sustainable development; green computing; data centre; energy efficiency; energy; computer and it